Pelaksanaan Gadai Tanah Pertanian di Desa Gumukmas Kecamatan Gumukmas Kabupaten Jember - Agil Nafista Agtihefa Irianto (University of Jember, 2016)
Law Number 56 PRP of 1960 concerning the Establishment of Agricultural Land Area has regulated how to redeem pawned land. In Gumukmas Village, Gumukmas Subdistrict, Jember Regency the practice of agricultural land pawning is still widely found in the community, this is due to the many factors that cause the people to mortgage their land. Forms of agreement regarding the redemption of pawning are also various following the agreement of the parties concerned. In some areas the pawning agreement is known by several terms, sende is a term of pawning used by Javanese indigenous people. Resale is one of the ways to redeem pawning land that applies in Gumukmas Village, that is, if the landowner cannot pay the pawning to the pawning holder within the time specified in the initial agreement, then the land that becomes the object of the pawn will be sold and the proceeds from the sale land are used to pay the mortgage and if the money from the sale is still left, it will be returned to the landowner. KEYWORDS: Fiduciary, Land, Farm Land, Pawn of Agricultural Land.